Theatre in Argentinian Patagonia. Comodoro Rivadavia and Sarmiento: a Different Experience of Theatre. (ALPHA. Journal of Arts, Literature and Philosophy, 2002)
The author of this article wonders if it is possible to apply Clifford Geertz’s concept of culture in Patagonia, in the sense that it is essentially a semiotic concept. Geertz agrees with Max Weber that man is an animal caught in a web of meaning that he himself has woven, so that culture is a complex fabric. Thus cultural analysis should not be an experimental science in the search of laws, but an interpretative science in search of meanings. Geertz says that he is looking for “the explanation, interpreting social expressions that are enigmatic on the surface”.Using these premises, the author postulates another way of examining and isolating certain ideas or concepts about Patagonia. Such an objective implies a rejection of the idea of savagery, which resulted from specific interest as well as ignorance and from thought centered elsewhere, in order to convert it into something else, with another content, in which its different ways of being in the world are not limited, where the reducing concept of culture can be expanded because it is being offered another dimension of the world, which far from undermining what the world has created, gives it new life.